Guanxi vs networking: Distinctive configurations of affect- and cognition-based trust in the networks of Chinese vs American managers - Chua, Roy Y J; Morris, Michael W; Ingram, Paul (Journal of International Business Studies, 2009)
This research investigates hypotheses about differences between Chinese and American managers in the configuration of trusting relationships within their professional networks. Consistent with hypotheses about Chinese familial collectivism, an egocentric network survey found that affect- and cognition-based trust were more intertwined for Chinese than for American managers. In addition, the effect of economic exchange on affect-based trust was more positive for Chinese than for Americans, whereas the effect of friendship was more positive for Americans than for Chinese. Finally, the extent to which a given relationship was highly embedded in ties to third parties increased cognition-based trust for Chinese but not for Americans. Implications for cultural research and international business practices are discussed.